2004
DOI: 10.1007/s12110-004-1012-x
|View full text |Cite
|
Sign up to set email alerts
|

Women’s work, child care, and helpers-at-the-nest in a hunter-gatherer society

Abstract: Considerable research on helpers-at-the-nest demonstrates the positive effects of firstborn daughters on a mother's reproductive success and the survival of her children compared with women who have firstborn sons. This research is largely restricted to agricultural settings. In the present study we ask: "Does 'daughter first' improve mothers' reproductive success in a hunting and gathering context?" Through an analysis of 84 postreproductive women in this population we find that the sex of the first-or second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 42 publications
0
49
0
Order By: Relevance
“…The role of child labor in familial economy has been addressed within the framework of the "helpers-at-the-nest" theory by biological anthropologists, especially as concerns maternal fertility (Hames and Draper 2004). However, in the present study, the hypothesis of a positive effect of sharing of tasks upon the nutritional status of mothers and their daughters cannot be completely dismissed.…”
Section: Discussionmentioning
confidence: 86%
“…The role of child labor in familial economy has been addressed within the framework of the "helpers-at-the-nest" theory by biological anthropologists, especially as concerns maternal fertility (Hames and Draper 2004). However, in the present study, the hypothesis of a positive effect of sharing of tasks upon the nutritional status of mothers and their daughters cannot be completely dismissed.…”
Section: Discussionmentioning
confidence: 86%
“…Hawkes et al 1998;Mace & Sear 2005), our research indicates that males are more important provisioners in the Ache and Hiwi. Hames & Draper (2004) recently suggested that the notable helper effect of female kin in previous studies may be limited to agricultural societies. If the provisioning patterns we report here are more typical of other foraging economies, it suggests that post-reproductive females contribute to increased grandoffspring survival in foragers through activities other than provisioning, or that the grandmother demographic Hunter -gatherers as cooperative breeders K. Hill & A. M. Hurtado 3867 effect may be limited mainly to farmers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, nursing women who lived with female helpers spent less time in domestic work. 42 In his seminal time-allocation study among the Ifaluk, Turke 35 showed that girls contribute substantially to the subsistence economy and that mothers who bore girls early in their reproductive careers had greater completed fertility than did those whose first-born children were boys (but see Hames and Draper 43 ). Children at work.…”
Section: Constraints On Reproductive Rate: Balancing Maternal Allocatmentioning
confidence: 99%